Some geotechnical properties of pure and waste gypsum for geoelectrical grounding applications - Mohd Yuhyi, Mohd Tadza; Nurmazuria, Mazelan; Nur Farahana, Yusri; Amizatulhani, Abdullah (Sciendo, 2014)
Natural occurring gypsum is a soft mineral consists of hydrated calcium sulphate, mainly used in cement industry. On the other hand, red gypsum (RG) is a waste generated from a sulphate process of ilmenite ore to acquire titanium dioxide. Due to the gypsum content in both materials are similar, it is expected that both gypsum type can be used for similar engineering applications. In this study, RG was tested and compared to pure gypsum for geoelectrical grounding applications. The geotechnical properties and plasticity characteristics were carefully measured and tested. In addition, X-ray fluorescence (XRF) was employed to study the chemical constituents of the materials. Test results showed that, the geotechnical properties of RG is different to that of white gypsum. The plasticity index (PI) of RG was 239.6% greater due to the presence of Fe ions. Surprisingly, the electrical resistivity of both material were found to be similar. It was also noted that, although the plasticity of pure gypsum is high, the plasticity of pure gypsum was found to be short lived primarily due to instantaneous exothermic reaction between water and semi-hydrated gypsum. The change in the plasticity also affected the resistivity as gypsum hardened after short duration. Based on the geotechnical and plasticity characteristics determined, RG was found to be a better as grounding material as compared to gypsum.